Pengaruh Konten Instagram @kotabalige terhadap Pemenuhan Kebutuhan Informasi Pengguna - Stevani Elga Tampubolon; Diana Khuntari; Arum Marwati (Kajian Administrasi Publik dan ilmu Komunikasi, 2026)
The rapid development of social media has made Instagram one of the primary platforms for information dissemination and digital communication. In the tourism sector, the public's demand for fast and easily accessible local information continues to increase, particularly regarding Balige City. The absence of an official government account as a central source of regional information has encouraged people to rely on social media, including the Instagram account @kotabalige, which actively provides content related to tourism, culture, culinary attractions, local businesses, and community activities. This study aims to analyze the influence of @kotabalige's Instagram content on users' information fulfillment. A quantitative approach with a survey method was employed involving 100 respondents selected through random sampling. Data were collected using a Likert-scale questionnaire and analyzed through simple linear regression using IBM SPSS Statistics 30. The results indicate that Instagram content has a positive and significant effect on users' information fulfillment, with a coefficient of determination value of 0.611. This means that 61.1% of information fulfillment is influenced by the quality of Instagram content. The findings demonstrate that relevant, visually appealing, and consistently updated content effectively supports users in obtaining local information while strengthening local digital communication.